Metode dan Media Penyuluhan yang Efektif Bagi Penyuluh Agama Kristen Non PNS Pada Masa Pandemi Covid 19 di Wilayah Bandung Raya - Agus Nugroho; Gery Altobely Seroh; Nathasya Suradi (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
The Covid 19 pandemic has made non-PNS Christian Religious Extension Officers unable to carry out their counseling duties as before the Covid 19 pandemic. Extension officers cannot freely gather members of the target group in one place. The number of members gathered is strictly limited. Between extension workers and members of the target group cannot interact freely. In any situation, counseling or coaching for members of the target group must continue to be carried out. This study aims to obtain effective methods and media in counseling during the Covid 19 Pandemic. This research is a quantitative study with survey methods and library research. The methods and media for effective counseling can facilitate the tasks of non-civil servant Christian religious instructors in the Greater Bandung Region during the Covid 19 pandemic.